1997
DOI: 10.1107/s0108768196009950
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Na3NdSi6O15.2H2O – a Layered Silicate with Paths for Possible Fast-Ion Conduction

Abstract: Hydrothermal investigations of the high silica region of the Na20-Nd203-SiO2 system, carried out in the search for new fast-ion conductors (FIC's), yielded the compound Na3NdSi6Ols.2H20 (sodium neodymium silicate). Single-crystal X-ray methods provided lattice constants of a=7.385(2), b=30.831(7) and c= 7.1168 (13) /~,, space group Cmm2, and 22 atoms in the asymmetric unit. With four formula units per unit cell, the calculated density is 2.68gcm -3. Refinement was carried out with 1113 independent structure fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 4 publications
3
5
0
Order By: Relevance
“…Crystallographic data are provided in Table 1. Complete structure determinations, reported elsewhere (Haile et al 1995(Haile et al , 1997Haile and Wuensch, unpublished manuscript), confirmed the ideal compositions deduced from the microprobe and thermogravimetric analyses.…”
Section: Synthesis and Phase Identificationsupporting
confidence: 72%
See 2 more Smart Citations
“…Crystallographic data are provided in Table 1. Complete structure determinations, reported elsewhere (Haile et al 1995(Haile et al , 1997Haile and Wuensch, unpublished manuscript), confirmed the ideal compositions deduced from the microprobe and thermogravimetric analyses.…”
Section: Synthesis and Phase Identificationsupporting
confidence: 72%
“…† Haile and Wuensch, to be published. ‡ Haile et al (1997). Related to a phase reported by Karpov et al (1977).…”
Section: Synthesis and Phase Identificationmentioning
confidence: 73%
See 1 more Smart Citation
“…Liebau, 1985;Haile et al, 1997) 4.1.2. Alkali coordination and position with respect to the silica sheet.…”
Section: Discussionmentioning
confidence: 99%
“…Their various crystal structures and high physical‐chemical stability are advantageous for uses in many fields of application. To the family of the alkali‐ion conductors belong the silicates LiYSiO 4 ,3 K 8 Nd 3 (Si 12 O 32 )(OH),4 Na 3 Nd(Si 6 O 15 )(H 2 O) 2 ,5 K 8 Nd 3 Si 12 O 32 (OH)6 and α‐K 3 Nd(Si 6 O 15 )(H 2 O) 2 7. Among tuneable optical materials a large number of silicates are known: K 7 Eu 3 Si 12 O 32 (H 2 O) 4 , K 7 Sm 3 Si 12 O 32 (H 2 O) 3 ,8 Na 3 LaSi 6 O 15 (H 2 O) 2.5 , Na 4.92 Sm 2.36 Si 12 O 30 (H 2 O) 4.88 ,9 K 3 TbSi 3 O 9 ,10 K 3 TbSi 3 O 8 (OH) 2 , K 3 ErSi 3 O 8 (OH) 2 , K 3 EuSi 3 O 8 (OH) 2 ,11 Na 3 ErSi 3 O 9 ,12 Na 3 TbSi 3 O 9 (H 2 O) 3 ,13 (Eu 8.18 Na 1.08 )(SiO 4 ) 6 (OH) 1.62 ,14 Na 2.4 Ce(Si 2 O 5 ) 3 (H 2 O) 2 15 and Eu‐, Er‐, Nd‐, Tb‐AV‐9‐type Na 4 K 2 Ln 2 Si 16 O 38 · 10 H 2 O 1618.…”
Section: Introductionmentioning
confidence: 99%